Quality of life of patients undergoing hymenoptera venom immunotherapy - Ewa Guz; Magdalena Brodowicz-Król (Kazimierz Wielki University, 2019)
Hymenoptera stings are one of the main causes of anaphylaxis in Europe [1] . Clinical observation shows that the most dangerous effects are those that develop immediately after the sting[2] . Most often, allergic symptoms occur within 5 to 20 minutes. There are reactions starting after 2 hours and sometimes even after 72 hours. The group of patients at risk of more severe reactions are atopic patients, patients with skin mastocytosis , the elderly, burdened with additional diseases. The highest mortality rate is observed in people over 50 years of age [3] . Aim : The aim of this study is to evaluate and compare parameters of quality of life, anxiety and anxiety among patients who have undergone immunotherapy for Hymenoptera venoms. Material and Methods : The research was conducted at the turn of January and February 2019. The study involved 100 patients desensitized to hymenoptera venoms in the Department of Allergology and Lung Diseases of the Provincial Specialist Hospital named after of Stefan Cardinal Wyszyński in Lublin. The diagnostic method that was used in the study was the diagnostic survey. The research tool used was the questionnaire: The World Health Organization Quality Of Life (WHOQOL) -BREF (short version of the questionnaire assessing the quality of life) extended by the author's questionnaire. The database was created and statistical analyzes were carried out based on Statistica 9.1 computer software. ( StatSoft, Poland).   Rezults : The vast majority of respondents said that their quality of life is good or very good. As much as 82% gave such an answer. Only seven of the respondents rated their quality of life as bad or very bad. 11% of respondents could not determine the level of quality of their lives. The respondents gave similar satisfaction to their health condition. As many as 74% of respondents declare that they are satisfied or very happy with their health. A quarter of the respondents could not determine whether they were satisfied or not about their health. Conclusion :      In allergy to hymenoptera insects, a significant impact of the disease on the emotional, professional, social and implemented sphere is observed. The previous experience of anaphylaxis symptoms plays a significant role here, but more importantly anxiety associated with their reoccurrence, which is usually the cause of a deterioration in comfort of life, a sense of security risk. That is why proper education conducted simultaneously with patients' immunotherapy is so important. This has a significant impact on the quality of life of patients allergic and immunotherapy to Hymenoptera venoms.